2012
DOI: 10.1242/dev.081679
|View full text |Cite
|
Sign up to set email alerts
|

Twist1 mediates repression of chondrogenesis by β-catenin to promote cranial bone progenitor specification

Abstract: SUMMARYThe bones of the mammalian skull vault form through intramembranous ossification. Skull bones ossify directly, in a process regulated by -catenin, instead of passing through a cartilage intermediate. We tested whether -catenin is necessary for fate selection of intramembranous bone progenitors in the skull. Here, we show in mice that removal of -catenin from skull bone progenitors results in the near complete transformation of the skull bones to cartilage, whereas constitutive -catenin activation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
109
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(115 citation statements)
references
References 60 publications
6
109
0
Order By: Relevance
“…G,H). The loss of Twist1 mRNA expression was consistent with our previous study on protein expression (Goodnough et al, ). However, the cranial mesenchyme in controls and β‐catenin mutants expressed skeletogenic identity markers, Msx2 and Dlx5 (Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…G,H). The loss of Twist1 mRNA expression was consistent with our previous study on protein expression (Goodnough et al, ). However, the cranial mesenchyme in controls and β‐catenin mutants expressed skeletogenic identity markers, Msx2 and Dlx5 (Fig.…”
Section: Resultssupporting
confidence: 92%
“…I–L). Domains of Dlx5 and Msx2 expression were expanded, revealing acquisition of ectopic skeletogenic identity in the supraorbital arch mesenchyme in these mutants (Goodnough et al, ). These results together demonstrated that ectoderm Wnts and mesenchyme Wnt/β‐catenin signaling are required for Twist1 mRNA expression in the cranial mesenchyme.…”
Section: Resultsmentioning
confidence: 99%
“…Twist1 also interacts with Runx2 as a target gene of Wnt signaling to regulate chondrocyte differentiation in vitro (Dong et al, 2007). Although Wnt/β-catenin directly activated Twist1 expression in skull progenitors, but conditional Twist1 deletion only partially phenocopied the absence of β-catenin, and Twist1 deletion also partially restored bone formation in the presence of constitutive β-catenin activation suggest other upstream factors may also involved in Twist1 regulation (Goodnough et al, 2012). In this study, we found that Twist1 highly expressed in MPCs, as well as NICD1, suggests that Twist1 may be required for NICD1 mediated maintainess of MPC stem cell-like phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The intracellular signaling pathway is transduced by β‐catenin which binds to TCF/LEF transcription factors to regulate gene transcription in diverse contexts during embryonic development (Brugmann et al, ; Cadigan & Nusse, ; Day et al, ; Gaur et al, ; Niemann et al, ). Of the three signaling pathways discussed in this review, conditional mutants of the Wnt signaling pathway result in the most dramatic skull bone defects with complete agenesis of the CNCC‐ and PM‐derived skull bones (Day et al, ; Goodnough et al, , ; Hill et al, ). During early skull bone development, Wnt/β‐catenin signaling is required for the proliferation and survival of craniofacial structures.…”
Section: Signaling Factors Regulating the Calvarial Bone Initiation Pmentioning
confidence: 99%